A Mini Review on COVID-19 Therapeutics: Current Status and Future Directions - Kaushik, Niranjan; Sharma, Vikram; Sharma, Vikas (Coronaviruses, 2021)
Corona viruses belong to the genus Corona virus with its high mutation rate in the Coronaviridae. In this review article, the focus is on current status of research against SARS-CoV-2, various mobile apps launched to diagnose COVID-19 infection and status of prospective therapies available against COVID-19 virus in this early stage of COVID-19 outbreak.
Keywords: Corornavirus